2016
DOI: 10.1177/1538574416655891
|View full text |Cite
|
Sign up to set email alerts
|

Successful Conservative Treatment of a Kommerell Aneurysm Associated With Right-Sided Aortic Arch

Abstract: Right-side aortic arch is a rare congenital aortic anomaly occurring in 0.05% to 0.1% of the general population. Approximately, half of these cases may be associated with an aberrant left subclavian artery and occasionally with aneurysmatic change at its origin known as Kommerell diverticulum or aneurysm (KA). Herein we report a challenging case of a right-side aortic arch associated with KA incidentally observed in a 73-year-old male with metastatic lung cancer. After careful multidisciplinary discussion, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Thoracic aortic endovascular repair and aortic arch debranching either endovascular or surgically are treatment options in patients with comorbidities. 2,8 In the present case, the patient was scheduled for close follow-up since surgery or endovascular intervention could not be performed due to comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…Thoracic aortic endovascular repair and aortic arch debranching either endovascular or surgically are treatment options in patients with comorbidities. 2,8 In the present case, the patient was scheduled for close follow-up since surgery or endovascular intervention could not be performed due to comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…They are extremely rare, as they can be found only in 3-8% of the KD [5][6][7]. Some authors have stated that a KA should be defined when the size of a KD is greater than 30 mm, since the risk of rupture (rKA) increases significantly, yet there is still no consensus [8,9]. Histological studies highlight that KA requires a separate categorisation that distinguishes them from KD, as it has been demonstrated that medial cystic necrosis is present in the vessel wall of the KA [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the implications of this condition, including death, emergent surgical repair is usually granted. Some elective surgical approaches have been proposed; however, evidence regarding the optimal emergent management for KA and rKA is mainly based on isolated case reports or a few KD cohorts, as shown in Table 1 [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the implications of this condition, including mortality, emergent surgical repair is usually granted. Some surgical approaches have been proposed; however, evidence regarding the optimal management for KA and rKA is mainly based on isolated case reports or a few KD cohorts, as shown in Table 1 (2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%